Hypokalaemic paralysis secondary to thiazide diuretic abuse: an unexpected outcome for cauda equina syndrome - Cawley, Derek T; Curtin, Paul T; McCabe, John P (Evidence-Based Spine-Care Journal, 2011)
Study design: Case report.We present the case of a 55-year-old woman with cauda equina syndrome, and hypokalaemic paralysis secondary to thiazide diuretic abuse.